2003
DOI: 10.1051/0004-6361:20031286
|View full text |Cite
|
Sign up to set email alerts
|

Carbon star survey in the Local Group

Abstract: Abstract. We present a CFH12K wide field survey of the carbon star population in and around NGC 3109. Carbon stars, the brightest members of the intermediate-age population, were found nearly exclusively in and near the disk of NGC 3109, ruling out the existence of an extensive intermediate-age halo like the one found in NGC 6822. Over 400 carbon stars identified have M I = −4.71, confirming the nearly universality of mean magnitude of C star populations in Local Group galaxies. Star counts over the field reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…The brightest sources with −8.4 < M bol < −6.0 mag tend to be in the central area, although they are too few in number to draw a definite conclusion. Demers et al (2003) found that the carbon stars are located almost exclusively in and near the disk for the Magellanic type galaxy NGC 3109. This is consistent with our results in the SMC and the LMC.…”
Section: The Small Magellanic Cloudmentioning
confidence: 99%
“…The brightest sources with −8.4 < M bol < −6.0 mag tend to be in the central area, although they are too few in number to draw a definite conclusion. Demers et al (2003) found that the carbon stars are located almost exclusively in and near the disk for the Magellanic type galaxy NGC 3109. This is consistent with our results in the SMC and the LMC.…”
Section: The Small Magellanic Cloudmentioning
confidence: 99%
“…Because of its proximity to us it turns out to be one of the brightest galaxies seen in the southern sky. Its carbon star population has been surveyed by Demers et al (2003) who identified over 400 C stars using the narrow band technique. Recently the near-infrared J and K s magnitudes of 77 Cepheids have been used by Soszyński et al (2006) to accurately determine the distance of NGC 3109.…”
Section: The Target Galaxiesmentioning
confidence: 99%
“…The small size of the images makes the astrometric and magnitude calibrations more difficult than for the SOFI data. For the astrometry we use as a reference the C star coordinates published by Demers et al (2003) and seen in the field. Because of the lack of suitable 2MASS stars, the magnitude calibration is done using the published J and K s magnitudes of the Cepheids (Soszyński et al 2006), taken on the same night as the images we analyse.…”
Section: Ngc 3109mentioning
confidence: 99%
“…Historically, these stars have attracted the attention of observers for several reasons: their characteristic observability due to the CN and C 2 bands in their spectra, their rarity (∼100 are presently known), and their high luminosity as AGB stars, which make them useful for studying the stellar content of the galactic halo at large distances (see for example Wallerstein & Knapp 1998;Totten & Irwin 1998, hereafter TI98). For illustration, in the I-band, Demers et al (2003) found from the study of several Local Group galaxies that the average I-band absolute magnitude of (not too dusty) AGB C stars is M I = −4.6. This average luminosity leads one to expect an apparent magnitude as bright as I = 15.4 for a distance of 100 kpc.…”
Section: Introductionmentioning
confidence: 99%